2006
DOI: 10.1068/c0528
|View full text |Cite
|
Sign up to set email alerts
|

Do Enterprise Support Programmes Leave Women Holding the Baby?

Abstract: Using data from a longitudinal study of working-class participants on a youth enterprise start-up programme in the UK, we examine whether programmes aimed at disadvantaged groups enable parents to combine business trading with childcare responsibilities. Business planning and programme selection practices ignored childcare, rendering it a solely private matter, invisible to public scrutiny. Yet this childcare barrier became both a cause and a consequence of business failure. Participants' experiences of combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 11 publications
0
71
0
1
Order By: Relevance
“…This in turn increases the cost of borrowing and/or leads to constraints in financing (Dunn and Holtz-Eakin 2000;Fairlie and Krashinsky 2012). Accordingly, those with lower levels of wealth and household income may not be able to compensate for the lack of external funds with their own financial resources and this then either prevents them from starting a new business or leads to undercapitalisation (MacDonald 1996;Marlow and Carter 2004;Rouse and Kitching 2006). However, others have challenged the financial constraints interpretation and have demonstrated that access to financial capital is not significantly associated with the probability of becoming an entrepreneur (Davidsson and Honig 2003;Kim et al 2006;Klyver and Schenkel, 2013).…”
Section: Financial Capital As a Resource For Entrepreneurshipmentioning
confidence: 99%
“…This in turn increases the cost of borrowing and/or leads to constraints in financing (Dunn and Holtz-Eakin 2000;Fairlie and Krashinsky 2012). Accordingly, those with lower levels of wealth and household income may not be able to compensate for the lack of external funds with their own financial resources and this then either prevents them from starting a new business or leads to undercapitalisation (MacDonald 1996;Marlow and Carter 2004;Rouse and Kitching 2006). However, others have challenged the financial constraints interpretation and have demonstrated that access to financial capital is not significantly associated with the probability of becoming an entrepreneur (Davidsson and Honig 2003;Kim et al 2006;Klyver and Schenkel, 2013).…”
Section: Financial Capital As a Resource For Entrepreneurshipmentioning
confidence: 99%
“…A large body of literature now recognizes the effect of family on work domains, illustrating how family can influence entrepreneurship through opportunity emergence and recognition, the decision to set up a new venture and access to resources. Family as a non-economic actor is increasingly being acknowledged as a 'critical factor in entrepreneurial activity in emerging economies' (Habbershon and pistrui 2002;Sabah, Carsrud, and Kocak 2014, 306), and has received much attention in the context of family businesses (Chirico and Bau 2014;Sabah, Carsrud, and Kocak 2014) and women's entrepreneurship (Rouse and Kitching 2006;Shivani, Mukherjee, and Sharan 2006); however, its implications for MWEs have not been sufficiently explored. One of the dominant characteristics of Indian culture is the importance placed on family as a central social unit and institution.…”
Section: Mixed Embeddedness Theory Explaining the Entrepreneurship Ofmentioning
confidence: 99%
“…Rouse and Kitching (2006) suggest that the family status of women entrepreneurs is a critical variable in research, as child-rearing problems contributed largely to the failure of their start-up businesses. On the contrary, the study of South Asian women entrepreneurs based in the U.K. found that the family as an institution not only supported the start-up of businesses but also provided monetary and other forms of support to enable the women to take the risk and, thus, played an important role in the success and growth of their business (Dhaliwal, Scott, and Hussain 2010).…”
Section: Mixed Embeddedness Theory Explaining the Entrepreneurship Ofmentioning
confidence: 99%
“…Consequently, policy interventions reflect tailored and bespoke support for: women-owned businesses (Marlow et al, 2008;Rouse and Kitching, 2006;Wilson et al, 2004); disabled people (Kitching, 2006); ethnic minorities and refugees (Deakins et al, 2003;Lyon et al, 2007;Ram and Smallbone, 2002;Ram et al, 2012); students and graduates (Pickernell et al, 2011); and rural enterprises (Anderson et al, 2005;Lee and Cowling, 2015;Smallbone et al, 2003;Sutherland and Burton, 2011).…”
Section: Entrepreneurship and Policymentioning
confidence: 99%